2018
DOI: 10.1088/1741-2552/aadb49
|View full text |Cite
|
Sign up to set email alerts
|

A novel re-attachable stereotactic frame for MRI-guided neuronavigation and its validation in a large animal and human cadaver model

Abstract: Objective. Stereotactic frame systems are the gold-standard for stereotactic surgeries, such as implantation of deep brain stimulation (DBS) devices for treatment of medically resistant neurologic and psychiatric disorders. However, frame-based systems require that the patient is awake with a stereotactic frame affixed to their head for the duration of the surgical planning and implantation of the DBS electrodes. While frameless systems are increasingly available, a reusable re-attachable frame system provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Preoperative imaging included a 3D-MPRAGE (1 mm isotropic resolution, FOV 25.6 × 25.6 cm, number of slices = 176, TR/TE: 1900/2.93 ms, flip angle = 9°). These images were brought into Slicer ( http://www.slicer.org ) ( Fedorov et al, 2012 ), registered with localization markers on the stereotactic frame using the SimpleStereotactic Slicer extension (J. Jacobs, UW Madison) ( Edwards et al, 2018 ), and registered to a swine atlas ( Félix et al, 1999 ; Saikali et al, 2010 ) using the Landmark Registration module (nonlinear, affine) in Slicer. An example is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative imaging included a 3D-MPRAGE (1 mm isotropic resolution, FOV 25.6 × 25.6 cm, number of slices = 176, TR/TE: 1900/2.93 ms, flip angle = 9°). These images were brought into Slicer ( http://www.slicer.org ) ( Fedorov et al, 2012 ), registered with localization markers on the stereotactic frame using the SimpleStereotactic Slicer extension (J. Jacobs, UW Madison) ( Edwards et al, 2018 ), and registered to a swine atlas ( Félix et al, 1999 ; Saikali et al, 2010 ) using the Landmark Registration module (nonlinear, affine) in Slicer. An example is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these studies, to our knowledge, only a few stereotactic head frames were shown to be compatible with the conventional Cosman Roberts Wells (CRW) Stereotactic System © . Most of the head frames were employed in studies with pig models, 9,12,13 with a design that could not easily be scaled to the ovine model, and was not suitable for clinical use, as reported by Oheim et al 10 …”
Section: Introductionmentioning
confidence: 99%
“…The stereotactic surgical approach has also been used for continuous monitoring of the electroencephalographic activity through the insertion of needles, as shown by Perentos et al 11 Despite these studies, to our knowledge, only a few stereotactic head frames were shown to be compatible with the conventional Cosman Roberts Wells (CRW) Stereotactic System © . Most of the head frames were employed in studies with pig models, 9,12,13 with a design that could not easily be scaled to the ovine model, and was not suitable for clinical use, as reported by Oheim et al 10 The present work focuses on the design of a new head frame system (HFS) for the ovine model, suitable for MRI and CT studies, designed to work with more widely available CRW Stereotactic System © . The new HFS was developed following clinical requirements for neurosurgical applications.…”
mentioning
confidence: 99%
“…Imaging technologies such as magnetic resonance imaging (MRI) provide visualization of brain structures that enable neurosurgeons to plan accurate and safe surgical trajectories (Edwards et al, 2017). In MRI-guided functional neurosurgery, image space is registered to a stereotactic head frame with a built-in three-dimensional (3D) coordinate system using stereotactic planning software (Edwards et al, 2018). This software allows surgeons to view the neuroimaging data to derive 3D coordinates of the brain target(s) to plan the surgical trajectory path(s).…”
Section: Introductionmentioning
confidence: 99%
“…This software allows surgeons to view the neuroimaging data to derive 3D coordinates of the brain target(s) to plan the surgical trajectory path(s). This approach has been predominantly used to implant electrodes for deep brain stimulation and to deliver focused ultrasonic ablation, both of which provide therapeutic relief of debilitating movement and psychiatric disorders (Elias et al, 2016;Edwards et al, 2017Edwards et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%